Effect of Intravenous Small‐Volume Hypertonic Sodium Bicarbonate, Sodium Chloride, and Glucose Solutions in Decreasing Plasma Potassium Concentration in Hyperkalemic Neonatal Calves with Diarrhea. (13th April 2017) - Trefz, F.M.; Constable, P.D.; Lorenz, I.
Abstract : Background: Hyperkalemia is a frequently observed electrolyte imbalance in dehydrated neonatal diarrheic calves that can result in skeletal muscle weakness and life‐threatening cardiac conduction abnormalities and arrhythmias. Hypothesis: Intravenous administration of a small‐volume hypertonic NaHCO3 solution is clinically more effective in decreasing the plasma potassium concentration ( c K) in hyperkalemic diarrheic calves than hypertonic NaCl or glucose solutions. Animals: Twenty‐two neonatal diarrheic calves with c K >5.8 mmol/L. Methods: Prospective randomized clinical trial. Calves randomly received either 8.4% NaHCO3 (6.4 mL/kg BW; n = 7), 7.5% NaCl (5 mL/kg BW; n = 8), or 46.2% glucose (5 mL/kg BW; n = 7) IV over 5 minutes and were subsequently allowed to suckle 2 L of an electrolyte solution. Infusions with NaHCO3 and NaCl provided an identical sodium load of 6.4 mmol/kg BW. Results: Hypertonic NaHCO3 infusions produced an immediate and sustained decrease in plasma c K. Hypertonic glucose infusions resulted in marked hyperglycemia and hyperinsulinemia, but c K remained unchanged for 20 minutes. Between 30 and 120 minutes after initiation of treatment, the most marked decrements in c K from baseline occurred in group NaHCO3, which were significantly ( P < .05) larger during this period of time than in calves in group NaCl, but not group glucose. After 120 minutes, the mean decrease in c K from baseline was −26 ± 10%, −9 ± 8%, and −22 ± 6% in groups NaHCO3, NaCl, and glucose, respectively. Conclusions/Clinical Importance: Small‐volume hypertonic NaHCO3 infusions appear to have clinical advantages for the rapid resuscitation of hyperkalemic diarrheic calves, compared to hypertonic NaCl or glucose solutions.